Tinjauan Yuridis Terhadap Pembuktian Hak Atas Tanah Menggunakan Eigendom Verponding Berdasarkan Peraturan Pemerintah (PP) Nomor 18 Tahun 2021: Studi Putusan 109/PK/PDT/2022 - Ahmad Akmal As Syauki; Dede Agus; Jarkasi Anwar (Journal of Law Perspectives Review, 2025)
This article examines the legal basis and evidentiary strength of using colonial-era Eigendom Verponding in proving land rights under Indonesia's contemporary agrarian law, particularly after Government Regulation (PP) No. 18 of 2021 on Land Management Rights, Land Rights, Condominium Units, and Land Registration. Focusing on Supreme Court Judicial Review Decision No. 109/PK/PDT/2022 concerning the Dago Elos dispute, we show that non-converted eigendom titles lost their validity as private rights after the 24 September 1980 deadline and became state-controlled land. Nevertheless, historical documents can still function as supporting evidence to prioritize applications for new rights by former holders, while physical possession without registered basis remains weak. Methodologically, the study adopts a normative juridical approach using statutory, case, and conceptual analyses. The findings reaffirm Indonesia’s negative publication system: certificates provide strong, not absolute, proof; and orderly conversion/registration is decisive. The article clarifies the evidentiary pathway for claims involving colonial titles post-PP 18/2021 and offers practical implications for BPN, judges, notaries/PPAT, and litigators.